Diseño de un modelode Gestión de Antención al Cliente para la Hosteria "EL TORIL" de la Ciudad de Riobamba. - Valarezo Espinosa, Carlos Michael (2010)
The present’s work it contains the problems that the employees of tourist establishments of lodging face that don't fulfill an attention to the appropriate client, to achieve the tourist's satisfaction inside their facilities. What justifies the development of the present investigation, with the main objective that is to “DESIGN A MANAGEMENT MODEL OF ATTENTION TO THE CLIENT FOR EL TORIL HOSTEL OF THE RIOBAMBA CITY” and specific objectives as: To diagnose the services and functions that it offers the Hostel the Bullpen, located in the city of Riobamba. To develop the pattern of Administration according to the necessities detected in the services of the hostel and to socialize the pattern of attention to the client with the personnel that works in the hostel, for their best understanding; that they will be good to end up developing the main objective. The work is structured in 5 chapters developed sequentially for its best understanding and annexes to supplement the investigation.